Intranasal nanocrystals of tadalafil: in vitro characterisation and in vivo pharmacokinetic study - Ruba S. Darweesh; Lubna A. Shriem; Nusaiba K. Al-Nemrawi (Pensoft Publishers, 2024)
Tadalafil (TDA) is a class II drug of the biopharmaceuticals classification system (BCS), with limited aqueous solubility and high permeability. This study aims to improve the bioavailability of poorly soluble tadalafil by developing intranasal nanocrystals (NCs) of TDA. TDA NCs that were stabilised by polyvinyl alcohol (PVA) had the lowest size and the best solubility. F11 had a 196 nm in size with PDI and zeta potential of 0.21 and -11.20, respectively, which shows 5.5 and 1.6-fold higher in solubility (9.37 ± 0.36 μg/mL) and dissolution (50.11 ± 1.69%) than pure tadalafil, respectively. An in vivo animal study demonstrated that the maximum plasma concentration (Cmax) and total area under the curve (AUC0∞) achieved in the TDA NCs group were 352.77 ± 35.17 ng/mL and 3377 ± 558 ng.h/mL, respectively, and were significantly higher than the pure TDA group after intranasal administration. In conclusion, TDA NCs were successfully prepared by the sonoprecipitation technique, with significant enhancement in in vitro and in vivo properties. Therefore, intranasal administration of TDA nanocrystals was a good model for the treatment of erectile dysfunction.